2013
DOI: 10.1111/jspn.12019
|View full text |Cite
|
Sign up to set email alerts
|

Integrating illness concerns into cognitive behavioral therapy for children and adolescents with inflammatory bowel disease and co‐occurring anxiety

Abstract: Anxiety screening and a mental health referral to professionals familiar with medical management issues is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 63 publications
(57 reference statements)
1
43
0
Order By: Relevance
“…Some studies allowed for the use of telephone sessions, sessions at home, or sessions at the same time/venue as medical appointments, to reduce the burden on families. This more flexible approach was particularly seen in the IBD studies,31 35 which also showed good patient satisfaction. Clinically, a more flexible approach would be a step towards creating services that are more accessible for this population.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Some studies allowed for the use of telephone sessions, sessions at home, or sessions at the same time/venue as medical appointments, to reduce the burden on families. This more flexible approach was particularly seen in the IBD studies,31 35 which also showed good patient satisfaction. Clinically, a more flexible approach would be a step towards creating services that are more accessible for this population.…”
Section: Discussionmentioning
confidence: 91%
“…In general, where outcomes related to physical health showed significant improvement, these were related to subjective measures (eg, pain scales, self-reported self-management); no consistent significant difference was found for objective measures of physical health, such as glycaemic control 28 29 31 33–35…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SCARED has been successfully implemented in various medical settings to screen for elevated anxiety in youth with a chronic illness (20,21) including IBD (22). A total sum score of 20 has been used as a cutoff score to identify children and adolescents with IBD in distress who may meet the criteria for a clinical anxiety disorder (22). Scores range from 0 to 82, with higher scores signifying higher distress.…”
Section: Anxiety Symptom Questionnairementioning
confidence: 99%